(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Strategically important and urgent tasks in Uzbekistan are to develop the welfare of the population and reduce poverty. The last event was the fight against poverty, consistently implemented in the economic policy of the state and turned into a national goal, which is the development of strategic programs and action plans of the Republic of Uzbekistan, employment in pandemic conditions, consistent use of economic methods of developed countries. with which it will be possible to manage the employment of the population.